Personal Dexterity (Eurasian Research Bulletin, 2022)
The proclamation of 2012 as the Year of the Family as a logical and consistent continuation of the Year of Harmonious Generation, the strengthening of measures to raise a healthy generation, the promotion of a generation of intellectual potential emphasize s the urgency of revitalization and strengthening. Following the program to build a free and prosperous homeland, free and prosperous life, our people have preserved their national, historical, spiritual and religious traditions, customs and traditions, wh ile at the same time studying new best practices in the world. Has been firmly on the path of creation and creativity for 20 years. Under the leadership ofPresident Islam Karimov, the architect of our independence, the architect of our national statehood, the initiator of all the great changes in our country, our people have set an example to the nations of the world in many respects. has been writing newachievements and milestones in gold letters.